Interference between immune cells and insomnia: a bibliometric analysis from 2000 to 2023 - Tang, Nana; Zeng, Yingjian; He, Guilian; Chen, Shupeng (Frontiers in Neurology, 2025)
BackgroundInsomnia is a widespread sleep disorder that significantly affects the quality of life and contributes to immune dysfunction, which in turn leads to chronic diseases. Despite extensive research on sleep disturbances and immune modulation, the relationship between insomnia and immune responses remains underexplored.ObjectivesThe primary objective of this study was to conduct a bibliometric analysis to explore the interaction between immune cells and insomnia, identifying key immune responses involved and their potential roles in the development of insomnia and associated comorbidities.MethodsA bibliometric analysis was conducted using data from the Web of Science Core Collection (WoSCC), focusing on research articles published between 2000 and 2023. The analysis aimed to identify trends, key research areas, and the role of immune system cells (T cells, B cells, NK cells, etc.) in insomnia.ResultsThe analysis revealed that various immune cells, including T cells, B cells, NK cells, neutrophils, and monocytes, play crucial roles in insomnia pathogenesis. These immune cells contribute to immune modulation and inflammatory responses, which are linked to sleep disturbances. The study also identified that insomnia is closely associated with comorbidities such as cardiovascular diseases, obesity, depression, and cancer, all of which involve immune dysfunction. The regulation of the immune system was found to be a key factor in improving sleep quality.ConclusionThis study provides valuable insights into the complex interaction between the immune system and insomnia. The findings underscore the importance of immune regulation in the treatment of insomnia, suggesting that future research should focus on integrating immune modulation into therapeutic strategies for insomnia. Further studies are needed to explore targeted therapies for immune-related insomnia and its comorbidities, emphasizing interdisciplinary research in this area.